Biodegradation Engineering and Technology - Chamy, Rolando; Rosenkranz, Francisca (IntechOpen, 2013)
This book contains a collection of different research activities where several technologies have been applied to the optimization of biodegradation processes. The book has three main sections: A) Hydrocarbons biodegradation, B) Biodegradation and anaerobic digestion, and C) Biodegradation and sustainability.